Mining of a Clinical Database: The Interpretation of Intense Serial Procalcitonin in the Prediction for Bloodstream Infection - Jiang, Zhiyi; Liu, Ning; Wang, Luhao; Wu, Jianfeng; Guan, Xiangdong (Frontiers in Medicine, 2021)
Background: Procalcitonin (PCT) was a promising biomarker for predicting infection. Bloodstream infection (BSI) is usually a deteriorating stage of sepsis. The purpose of this study was to explore the predictive value of intense serial procalcitonin assays for bloodstream infection in ICU. Methods: This study was a retrospective study based on a clinical database. We analyzed the data of critical patients from February 2016 to May 2020. The patients who received procalcitonin assays and blood cultures (BC) were classified into 4 groups according to the blood cultures: i) BC negative, ii) bacteria positive, iii) fungi-positive, iv) combined-positive, and the patients with bacteremia were further subdivided into Gram+ and Gram- bacteremia. Results: The database included 11219 patients. There were 3593 patients met the criteria for the analysis. The procalcitonin concentration differed significantly across BC groups (p < 0.0001). The fluctuation of PCT significantly increased in the BC positive groups (p < 0.0001). According to the ROC, the optimum cut-off of the fluctuation of PCT was around 8ng/ml for predicting BSI. Conclusion: Our study indicated that the fluctuation of PCT could be an indicator for screening BSI. With a fluctuation of PCT less than 8 ng/ml, BSI should not be a reasonable cause for sepsis exacerbating. The predictive value of PCT assay for gram-positive bacteremia was limited.